Wives and Property: Reform of the Married Women's Property Law in Nineteenth-Century England - Smith, Bonnie G. (Labour / Le Travail, 1985)
This article reviews the book, "Wives and Property: Reform of the Married Women's Property Law in Nineteenth-Century England," by Lee Holcombe.
Keywords: HOLCOMBE, Lee; MARRIED women -- Legal status, laws, etc.; Nonfiction; REVIEWS; WIVES & Property: Reform of the Married Women's Property Law in 19th-Century England (Book); books